2015
DOI: 10.18488/journal.23/2015.4.1/23.1.10.19
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Direct Vs. Indirect Written Corrective Feedback on L2 Learners Written Accuracy in EFL Context

Abstract: New challenges are coming in the present globalized world of 21 th century that consequently has required deep changes in educational process, since the 21 th century requires more creativity, critical thinking, problem solving as well as communicative skills. English, as the main international language, is playing an important role in the globalized world's people's life, so the scholars try to use more sophisticated learning methods in EFL scope. The present study was an attempt to investigate the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
3
7
1
2
Order By: Relevance
“…Those studies and many others assured that there is no significant difference between direct versus indirect modes of corrective feedback in developing linguistic aspects. The results however are not consistent with other studies, which Journal of Research in Curriculum, Instruction and Educational Technology reported that direct corrective feedback is more fruitful than indirect corrective feedback (Almasi & Tabrizi, 2016;Salimi & Ahmadpour, 2015;Shirazi & Shekarabi, 2013;Suh, 2014); or those studies which showed that indirect corrective has productive effects than direct corrective feedback (Baleghizadeh & Dadashi, 2011;Eslami, 2014;Ghandi, & Maghsoudi, 2014, Hosseiny 2014.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Those studies and many others assured that there is no significant difference between direct versus indirect modes of corrective feedback in developing linguistic aspects. The results however are not consistent with other studies, which Journal of Research in Curriculum, Instruction and Educational Technology reported that direct corrective feedback is more fruitful than indirect corrective feedback (Almasi & Tabrizi, 2016;Salimi & Ahmadpour, 2015;Shirazi & Shekarabi, 2013;Suh, 2014); or those studies which showed that indirect corrective has productive effects than direct corrective feedback (Baleghizadeh & Dadashi, 2011;Eslami, 2014;Ghandi, & Maghsoudi, 2014, Hosseiny 2014.…”
Section: Discussioncontrasting
confidence: 88%
“…The results attained concerning the effectiveness of direct corrective feedback are in line with those of some studies (Ferris, & Helt, 2000;Van Beuningen, et al 2012;Jokar & Soyoof, 2014;Salimi & Ahmadpour, 2015;and Almasi and Tabrizi, 2016) which reported that the direct corrective feedback on errors help the learners improve accuracy in their writing. The results however are different from some others, which reported that the corrective feedback on grammatical errors could not assist the learners to improve accuracy in their writing (Truscott& Hsu, 2008) as they depend on a small sample consisted of 21 students in the ESL context.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Desde un punto cognitivo, el FCMD implicaría una carga menor que la que ejerce el FCMI puesto que en este último caso es el estudiante el que tiene que examinar el problema lingüístico a un nivel más profundo y de mayor elaboración para resolverlo, comparado con el Feedback Correctivo Escrito Directo (FCMD) (Ferris, 2010). Por dicho argumento se plantea que el Feedback Correctivo Escrito Indirecto (FCMI) sería más conducente a la adquisición de largo plazo que el FCMD (Bitchener & Ferris, 2012;Ferreira, 2017aFerreira, , 2017bSalimi & Ahmadpour, 2015;Elejalde & Ferreira, 2018).…”
Section: Tratamiento De Los Errores Para La Precisión Escritaunclassified
“…Yazılı düzeltme geribildirimi, öğretmen ya da akran tarafından öğrencinin oluşturduğu taslak metinde yer alan yanlışlara yönelik doğrudan ve dolaylı yoldan sağlanan bildirimleri kapsar. Son yıllarda öğrencilerin yazma gelişiminde öğretmen geribildiriminin etkisi üzerine çalışmaların yoğunlaştığı görülmektedir (Lalande 1982;Shepard 1992;Frantzen 1995;Ferris & Helt 2000;Ferris 2002;Ferris 2006;Van Beuningen, De Jong & Kuiken 2008;Ellis 2009;Herrera 2011;Salimi & Ahmadpour 2015). Alan yazında yer alan çalışmaların bulguları incelendiğinde, anadilinde (bundan sonra D1) ve yabancı dilde (bundan sonra D2) yazma sürecinin benzer yönleri olduğu gibi, D2 yazma sürecinin bazı yönleriyle kendine özgü bir süreci barındırdığı söylenebilir.…”
unclassified